Ubiquitin ligase Siah2 regulates RevErbα degradation and the mammalian circadian clock - DeBruyne, Jason P. (Proc Natl Acad Sci U S A, 2015)
Regulated degradation of proteins by the proteasome is often critical to their function in dynamic cellular pathways. The molecular clock underlying mammalian circadian rhythms relies on the rhythmic expression and degradation of its core components. However, because the tools available for identifying the mechanisms underlying the degradation of a specific protein are limited, the mechanisms regulating clock protein degradation are only beginning to be elucidated. Here we describe a cell-based functional screening approach designed to quickly identify the ubiquitin E3 ligases that induce the degradation of potentially any protein of interest. We screened the nuclear hormone receptor RevErbα (Nr1d1), a key constituent of the mammalian circadian clock, for E3 ligases that regulate its stability and found Seven in absentia2 (Siah2) to be a key regulator of RevErbα stability. Previously implicated in hypoxia signaling, Siah2 overexpression destabilizes RevErbα/β, and siRNA depletion of Siah2 stabilizes endogenous RevErbα. Moreover, Siah2 depletion delays circadian degradation of RevErbα and lengthens period length. These results demonstrate the utility of functional screening approaches for identifying regulators of protein stability and reveal Siah2 as a previously unidentified circadian clockwork regulator that mediates circadian RevErbα turnover.